CMS Phase-1 pixel detector refurbishment during LS2 and readiness towards the LHC Run 3. (1st September 2022) - Noehte, Lars O. S.; ,
Abstract: The CMS Phase-1 pixel detector was extracted from the underground cavern after the end of the LHC Run 2 in 2019 and has been kept cold to protect the silicon sensors during the long shutdown period (LS2) in 2019–2021. The LHC is now preparing for the next period of data taking, Run 3, which is scheduled to start in spring 2022. The Phase-1 pixel detector was going through a series of refurbishment and repairs this year to improve the quality of the collected data and enhance the detector performance. The innermost barrel pixel layer has been replaced with new modules and features improved front-end readout chips (PROC600v4), token bit manager chips (TBM10d), and circuit boards to rectify the issues discovered in Run 2. The forward pixel detector has been equipped with new cooling inlets for safe handling and features a revised high-voltage power distribution scheme to better match the low-voltage granularity. All the DC-DC converter modules have been replaced with new modules featuring an improved FEAST2.3 ASIC, which is considerably more robust against the total ionizing dose effect and thus prevents them from breaking during operation. Overall, this article will summarize the refurbishment work of the pixel detector during LS2, and highlight the readiness towards the LHC Run 3 after installation and commissioning.